1996
DOI: 10.1007/bf00144625
|View full text |Cite
|
Sign up to set email alerts
|

Purification, spectroscopic analysis and biological activity of the macrocyclic dihydroxamate siderophore alcaligin produced by Bordetella pertussis and Bordetella bronchiseptica

Abstract: Hydroxamate siderophores of virulent Bordetella pertussis and Bordetella bronchiseptica strains were purified using a simple large-scale isolation procedure, and identified by various spectroscopic techniques as the macrocyclic dihydroxamate siderophore trivially known as alcaligin, 1,8(S),11,18(S)- tetrahydroxy-1,6,11,16-tetraazacycloeicosane-2,5,12,15-tetrone+ ++, which was previously isolated from the taxonomically-related bacterial species Alcaligenes denitrificans subsp. xylosoxydans. Alcaligin purified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 25 publications
3
73
0
Order By: Relevance
“…The dihydroxamate molecule can thus be considered a cyclic dimer of two structural units consisting of 1-amino-4-(N-hydroxylamino)-2(S)-butanol and succinic acid. Consistent with this twofold symmetric structure, high-resolution proton and carbon nuclear magnetic resonance spectroscopy recently determined that the molecule displays a twofold symmetric conformation in aqueous solution, although evidence suggests that multiple C 2 -symmetric conformations of alcaligin coexist in aqueous and methanolic solution (10). Alcaligin shares structural features with the ferrioxamine family of siderophores (30), which are produced by actinomycetes as well as certain enterobacterial species such as H. alvei (55).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The dihydroxamate molecule can thus be considered a cyclic dimer of two structural units consisting of 1-amino-4-(N-hydroxylamino)-2(S)-butanol and succinic acid. Consistent with this twofold symmetric structure, high-resolution proton and carbon nuclear magnetic resonance spectroscopy recently determined that the molecule displays a twofold symmetric conformation in aqueous solution, although evidence suggests that multiple C 2 -symmetric conformations of alcaligin coexist in aqueous and methanolic solution (10). Alcaligin shares structural features with the ferrioxamine family of siderophores (30), which are produced by actinomycetes as well as certain enterobacterial species such as H. alvei (55).…”
Section: Discussionmentioning
confidence: 95%
“…Evidence for biological activity of the purified siderophores was gathered with growth stimulation and 55 Fealcaligin transport assays of Bordetella spp. (10). Uptake rates and saturability of iron uptake observed in 55 Fe transport assays were indicative of a high-affinity ferric alcaligin transport system and provided the first direct evidence, beyond simple growth stimulation assays, of alcaligin-mediated Bordetella iron transport.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Armstrong and Clements isolated and characterized B. bronchiseptica transposon-induced siderophore-deficient mutants; DNA hybridization studies using sequences flanking those transposon insertions confirmed the existence of homologs of B. bronchiseptica siderophore system genes in B. pertussis (6). The siderophores of B. pertussis and B. bronchiseptica have been characterized structurally, and each has been identified as the macrocyclic dihydroxamate siderophore known as alcaligin (11,37), previously isolated from the taxonomically related bacterial species Alcaligenes denitrificans subsp. xylosoxydans (41,42).…”
mentioning
confidence: 94%